a: \(\Leftrightarrow y\left(y^{199}-1\right)=0\)
=>y=0 hoặc y=1
b: \(\Leftrightarrow y^{2008}\left(y^2-1\right)=0\)
hay \(y\in\left\{0;1;-1\right\}\)
c: \(\Leftrightarrow\left(2y-1\right)\cdot\left[\left(2y-1\right)^{49}-1\right]=0\)
=>2y-1=0 hoặc 2y-1=1
=>y=1/2 hoặc y=1
`y^200 = y`
`=> y^200 = y^200`
`=> y =y`
`=> y = 1; 0`
Vậy `y = 1` hoặc `y = 0`
_____________________________
`y^2008 = y^2010`
`=> y^2010 = y^2008`
`=> y^2008 . y^2 = y^2008.1`
`y^2 = 1`
`=> y^2 = ` \(\left\{{}\begin{matrix}y=-1\\y=1\end{matrix}\right.\)
Vậy `y = -1` hoặc `y = 1`
\( y^2\)\(^0\)\(^0\)\(=y\)
\(=> y^2\)\(^0\)\(^0\)\(-y=0\)
\(<=>y(y^1\)\(^9\)\(^9\)\(-1)=0 \)
\(=>\left[{}\begin{matrix}y=0\\y^{199}=1\end{matrix}\right.< =>\left[{}\begin{matrix}y=0\\y=1\end{matrix}\right.\)
\(y^{200}=y\)
\(y^{200}-y=0\)
\(y\left(y^{199}-1\right)=0\)
=> y=0 hoặc \(y^{199}-1=0\)
\(y^{199}=1\)
y=1
\(y^{2008}=y^{2010}\)
\(y^{2008}-y^{2010}=0\)
\(y^{2008}\left(1-y^2\right)=0\)
=> \(y^{2008}=0\) hoặc \(1-y^2=0\)
y=0 \(y^2=1\)
=> y=1 hoặc y=-1
\(\left(2y-1\right)^{50}=2y-1\)
\(\left(2y-1\right)^{50}-\left(2y-1\right)=0\)
\(\left(2y-1\right)\left[\left(2y-1\right)^{49}-1\right]=0\)
=> 2y-1=0 hoặc \(\left(2y-1\right)^{49}-1=0\)
2y=1 \(\left(2y-1\right)^{49}=1\)
\(y=\dfrac{1}{2}\) \(2y-1=1\)
2y=2
y=1
\(\left(\dfrac{y}{3}-5\right)^{2000}=\left(\dfrac{y}{3}-5\right)^{2008}\)
\(\left(\dfrac{y}{3}-5\right)^{2000}-\left(\dfrac{y}{3}-5\right)^{2008}=0\)
\(\left(\dfrac{y}{3}-5\right)^{2000}\left[1-\left(\dfrac{y}{3}-5\right)^8\right]=0\)
=> \(\left(\dfrac{y}{3}-5\right)^{2000}=0\) hoặc \(1-\left(\dfrac{y}{3}-5\right)^8=0\)
\(\dfrac{y}{3}-5=0\) \(\left(\dfrac{y}{3}-5\right)^8=1\)
y=15 y=18